Cutaneous laser surgery for secondary burn reconstruction: Cost benefit analysis. Issue 3 (May 2020) - Azzopardi, Ernest A.; Duncan, Robert T.; Kearns, Mollie; Marangoni, Francesco; Ibrahim, Nader; Azzopardi, Ernest A.F.; Boyce, Dean; Tretti, Matteo; Mursion, Maxwell S.C.
Highlights: We provide Current best evidence to suggest that a laser service is economically sustainable. Like-for-Like, cutaneous laser surgery is financially more efficient than traditional surgery as a meditum-long term investment. Procedural coding is currently unsatisfactory and needs to be addressed as a matter of priority. Superspecialist training is required. Abstract: Thermal disease presents a major burden to individual patient morbidity, healthcare cost as well as to over all economy. Burns also also represent a significant per-patient utlilisation of finite healthcare resources. Secondary complications in these patients, such as multiple drug resistant organisms, may have a devastating effect. Laser surgery has recently come of age as an optimal tool in the secondary reconstruction of burn injury, that is able to simultaneously address significant sheet scar tightness, hypertrophic, atrophic, and keloid complications, pruritus, microstomia, ectropion, skin graft honeycombing, and improve range of movement whilst reducing the risk of infection to <1%. Yet, cutaneous laser surgery is often underutilised due to the perceived concerns about the sustainability of a new service with relatively high startup cost. We present a dual methodology to explore this concern: an evidence-based background review of the last 5 years of current best evidence, and a 22-year cost-analysis comparison at an established, high volume UK Centre of reconstructive surgery. We report that fiscal viability for laser surgery services for secondary burn reconstruction is supported by: level 2 (one systematic review) level 4 evidence (2 studies) and level 5 evidence (expert reports). Evidence over 22 years from an established super-regional NHS laser centre shows that introduction of this service led to sustained and substantial cost saving, producing excellent surgical results at a fraction of the cost of traditional surgery. Analysis of the potential dollar-effect of these advantages to the general population supports state investment in expertise and capital equipment as a medium to long-term cost saving strategy, which may also aid re-integrating patients into the workforce making a meaningful contribution to the economy.